The frequency of asymptomatic urinary system abnormalities in children detected with cineurography imaging during angiocardiography. (20th February 2019) - Oral, Orcun; Toprak, Muhammet Hamza Halil; Uysal, Fahrettin; Bostan, Ozlem Mehtap; Cil, Ergun
Abstract: Introduction: Diagnostic and interventional catheter angiography of the heart is frequently used in paediatric cardiology. It is also possible to detect urinary system anomalies with cineurography images that may be obtained during angiocardiography. In this study, the aim was to determine the frequency, distribution, and properties of urinary system anomalies accompanying heart diseases, and to find out the effectiveness of cineurographic images in detecting the urinary system anomalies. Methods: The cineurographic images of 2022 children who had undergone angiocardiography between 1995 and 2015 were retrospectively examined. Results: Urinary system anomalies were detected in 261 of the 2022 cases (12.9%). Of these 261 cases, 148 were males (56.7%), whereas 113 were females (43.3%). Among the heart diseases, the group most accompanied by urinary system anomalies was the non-cyanotic left-to-right shunted heart diseases, which was detected in 120 (39.1%) patients. Pelvicalyceal ectasia was the most common urinary system anomaly encountered and was detected in 89 patients (34.1%). Of the urinary system anomalies cases, 94 detected by cineurography were determined to be clinically severe. When the effectiveness of the cineurography was evaluated using the ultrasonography records of the patients, it was found to have 63.8% accuracy. Conclusion: Many of the patients with CHDs concomitantly have urinary system anomalies. It is possible to determine asymptomatic urinary system anomalies using cineurographic imaging during angiocardiography. This may lead to earlier treatments and improved prognosis for the patients, thus making it possible to prevent potential future problems.